Reviews: Толковый словарь якутского языка/Саха тылын быhаарыылаах тылдьыта (Explanatory dictionary of the Yakut language [in fifteen volumes], in the text bellow referred to as or ). Под общей редакцией академика Академии наук Респу-блики Саха (Якутия) П[ётра] А[лексеевича] Слепцова/Caxa Oрoспyyбyлyкэтин Наукатын академиятын академига П.А. Слепцов уопсай эрэдээксийэтинэн (under the general editorship of academician P[yotr] A[lekseyevich] Sleptsov of the Sakha [Yakut] Academy of Sciences). 2004- - Majewicz, Alfred F. (Lingua Posnaniensis, 2020)
Review